2019
DOI: 10.1017/s1754470x18000296
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the transition from BAME community mental health worker to IAPT low intensity psychological wellbeing practitioner

Abstract: The Improving Access to Psychological Therapies (IAPT) programme started in 2008, but it contained little provision for specifically meeting the needs of Black, Asian and minority ethnic (BAME) groups. The purpose of this evaluation was to describe the experience of transition from BAME community mental health worker (CMHW) to IAPT low-intensity psychological wellbeing practitioner (PWP) in order to identify possible gains and losses for the former communities served, and the factors that might contribute to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In an effort to make IAPT services more accessible Community Mental Health Workers (CMHW’s) were recruited to offer culturally adapted treatment as Psychological Wellbeing Practitioners (PWP’s) in Sheffield. Hakim and Thompason (2019) explored the experiences of CMHW’s as PWP’s working with BAME’s in IAPT. They found that IAPT was inaccessible for South Asians as IAPT’s treatment approach was too structured for BAME clients.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to make IAPT services more accessible Community Mental Health Workers (CMHW’s) were recruited to offer culturally adapted treatment as Psychological Wellbeing Practitioners (PWP’s) in Sheffield. Hakim and Thompason (2019) explored the experiences of CMHW’s as PWP’s working with BAME’s in IAPT. They found that IAPT was inaccessible for South Asians as IAPT’s treatment approach was too structured for BAME clients.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of the transition from the BAME community mental health worker to IAPT lowintensity psychological wellbeing practitioner (Hakim et al, 2019) Hakim et al (2019) explored the experience of four IAPT low-intensity Psychological Wellbeing Practitioners (PWP) who had previously worked as BME Community Mental Health Workers (CMHW). The participants reported that low-intensity CBT (LiCBT) was useful, but only when cultural adaptations were made.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The first article discusses the need for service change to improve access to culturally adapted therapy (Beck and Naz, 2019). The second article describes an evaluation of the transition from the Black, Asian and minority ethnic (BME) community mental health worker to the IAPT low-intensity psychological wellbeing practitioner (Hakim et al , 2019). The third article discusses issues of race, cthnicity and culture in CBT to support therapists and service managers to deliver culturally competent therapy (Naz et al , 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It met the minimum sample requirement to achieve thematic saturation, the point at which no new information are generated from the data (Braun and Clarke, 2019b). Related studies also used a similar sample size (Hakim et al , 2019; Robinson et al , 2012).…”
Section: Methodsmentioning
confidence: 99%